The role of community engagement toward ensuring healthy lives: a case study of COVID-19 management in two Ghanaian municipalities - Aberese-Ako, Matilda; Doegah, Phidelia Theresa; Kpodo, Lebene; Ebelin, Wisdom; Kuatewo, Mawulom; Baba, Atubiga Alobit; Kpordorlor, Atsu Godsway; Lissah, Samuel Yaw; Kuug, Anthony Kolsabilik; Ansah, Evelyn (Frontiers in Public Health, 2024)
Community engagement is important for achieving success in the implementation of public health interventions and in the fight against pandemics, which is crucial for the attainment of SDG 3. Community engagement helps to understand the context of disease and health challenges, which facilitates designing context-specific solutions for the prevention of disease and in response to other health needs. Specifically, to understand issues about COVID-19 management and vaccine hesitancy and increase its acceptance, studies focus21qed on factors pertaining to the individual. However, the importance of community engagement in achieving such country and global goal in this instance has been overlooked. Therefore, to improve COVID-19 management and vaccine acceptance, there is a need for community engagement.This qualitative study therefore explored on one hand how government institutions embarked on community engagement in two municipalities, using the World Health Organization's community engagement framework, and on the other hand how community members experienced the engagement process. The study sums up with lessons learnt that can be applied to addressing other health problems towards Ghana's attainment of sustainable development goal 3 (SDG 3), which aims at promoting the wellbeing of all persons as well as fostering healthy lives.